Real‐world feasibility of short‐term, unsupervised home spirometry in CF. Issue 12 (27th September 2022) - Davis, Jaclyn; Ryan, Morgan; Marchetti, Peter; Dahlberg, Suzanne E.; Greenberg, Jonathan; Bacon, Callie; Kaur, Ravneet; Scalia, Sarah; Sawicki, Gregory S.
Abstract: Objectives: The objective of this study was to study the performance of two available home spirometers used by people with Cystic Fibrosis (PwCF) over a short‐term period and to assess user experience. Study design: This was a prospective observational study. Participants age 6 years and older were recruited to participate if they could complete acceptable spirometry in the clinic setting. Methods: Participants used either the NuvoAir Air Next or the ZEPHYRx MIR Spirobank Smart spirometer. They underwent a one‐time virtual training session, then completed 2 weeks of daily spirometry followed by 2 months of weekly spirometry. Participants responded to surveys and completed a debrief interview to understand user experience. Statistical analyses examined feasibility, reliability, and accuracy of each spirometer in an unsupervised, real‐world setting. Results: We report high adherence (80% [95% CI 61%–92%]) to our study protocol in all session attempts, but lower rates of adherence after discarding sessions performed with inadequate technique (47% [95% CI 28%–66%] to 63% [95% CI 44%–80%]). We found high reliability of each device by analyzing day‐to‐day variability and good concordance to recent in‐clinic testing (NuvoAir r  = 0.91 [0.82–0.93]; ZEPHYRx r  = 0.70 [0.45–0.84]). Patient experience in this cohort was favorable with most reporting ease of use and reassurance knowing lung function was being tracked over time. Conclusions: This real‐world study showed good performance of two different available home spirometers used by children and adults with CF. While overall adherence was high, suboptimal technique reduced the total interpretable data, possibly limiting feasibility. Future work should focus on developing sustainable training and coaching programs to support the success of home spirometry in a CF chronic care model.